Efektivitas Pembelajaran Berbasis Masalah (Problem Based Learning) terhadap Peningkatan Berpikir Kritis Siswa pada Mata Pelajaran Fiqih - Lela Maidayanti (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
Effective learning is reflected in the extent to which learning objectives can be achieved. This study aims to examine how the planning, implementation, and evaluation of Fiqh learning using the Problem Based Learning (PBL) model in measuring the critical thinking skills of students in grades VII to IX at MTs Salafuyah Purwakarta. This study uses a qualitative approach involving teachers and students as the main subjects. Data were obtained through field observations, documentation, and interviews with teachers and students, which were then analyzed using domain, taxonomy, and componential analysis techniques. The results of the study indicate that the Fiqh learning planning in grades VIII and IX has been prepared in accordance with the Learning Implementation Plan (RPP) which refers to the steps of the PBL model. The learning implementation process also follows the stages in the model, with the teacher acting as a facilitator, including providing internet access to support learning activities. Learning evaluation includes cognitive, affective, and psychomotor aspects. The results of students' critical thinking skills show that grade VII students are in the fairly critical category, while grade VIII and IX students are included in the critical category.